Leveling the Playing Field: Financial Regulation and Disappearing Local Bias of Institutional Investors - BERNILE, Gennaro (Institutional Knowledge at Singapore Management University, 2014)
This study examines how changes in firms’ information environment affect local agents. We show that local bias and informational advantage of institutional investors and equity analysts located around corporate headquarters decline sharply following the adoption of Regulation Fair Disclosure and Sarbanes-Oxley Act. The decline in local bias is more salient among firms whose information environment is more opaque before the new rules. At the aggregate market level, the degree of informed trading attributed to local investors also declines. Overall, the evidence is consistent with disclosure regulation affecting the informational advantage that market participants enjoy due to their proximity to firms.